Physics-Informed online characterization of Mixed-Face geology along tunnel alignments integrating Multi-Source information - Penghui Lin; Siyu Lu; Chao Shi (Tunnelling and Underground Space Technology, 2027)

Mitochondrial dysfunction in hypertension: mechanistic pathways and therapeutic implications - Jiao Tian; Lin Yi; Yuyuan Lu; Yushun Kou; Lingna Zhang; Penghui Jin; Xiaoke Wang; Tao Wu; Xin Yang; Yiyuan Wang; Ruiling Ma (Functional & Integrative Genomics, 2026)

Selective recovery of palladium from actual acidic wastewater using a covalent triazine framework: The critical enabling role of chloride ions - Junyi Yu; Qingying Xiao; Ziwen Chang; Jianzhi Zhang; Hao Dong; Jiaochan Zhong; Lin Ding; Yidi Chen; Xubiao Luo; Penghui Shao (Water Research, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Asymmetric coordination configuration unlocks single-atom nanozyme catalytic activity for redox-immune homeostasis and temporomandibular joint osteoarthritis therapy via macrophage depolarization and cGAS-STING pathway inhibition - Kaixun He; Hanyu Lin; Penghui Wei; Hongjia Zheng; Zhonghan Chen; Sihui Zhang; Yanjing Ou; Wenting Jiang; Wenxiu Yuan; Geyuan Zheng; Jiang Chen; Yi Zuo; et al. (Chemical Engineering Journal, 2026)

Joule-thermal desert-beetle-inspired mesh for efficient purification of viscous emulsified kitchen oil - Jiawei Sun; Runtang Cai; Xiangyu Huang; Jialuo Dai; Huan Fu; Xinjuan Zeng; Limiao Lin; Penghui Li; Min Zhang (Journal of Water Process Engineering, 2026)

Machine learning Identifies the impacts of the Eastern route of the South-to-North water diversion Project on the transformation of dissolved organic matter - Na Huang; Penghui Li; Yilan Jiang; Lin Chen; Dawei Wang (Journal of Hydrology, 2026)

Socioeconomic drivers of riverine biochemical oxygen demand: Insights from interpretable machine learning - Na Huang; Dawei Wang; Penghui Li; Lin Chen; Wei Wang; Zeng Zhou; Pei Xu; Sile Li; Yali Zhang; Yilan Jiang (Journal of Environmental Management, 2026)

Cation dependent dynamics of sequential and cotransport processes of micro-polystyrene and soil colloids in porous media - Qing Lin; Penghui Lin; Fengrui Wang; Haiyan Zhang; Jiaqi Gong; Shuhua Ji; Shaohui Xu; Xilin She (Environmental Research, 2026)

Ion chromatography–ultra-high-resolution mass spectrometry reveals EZH2-driven reprogramming of nucleic acid and protein methylation - Mohamed M.Y. Kaddah; Teresa W-M. Fan; Jahid M.M. Islam; Penghui Lin; Teresa A. Cassel; Richard Cunningham; Tom Brown; Richard M. Higashi; Andrew N. Lane (Analytica Chimica Acta, 2026)

Heterodimeric prodrug nanoassembly overcomes chemoresistance and ignites immunotherapy in glioblastoma - Guanting Li; Shunzhe Zheng; Penghui Wei; Haonan Li; Meixiu Lu; Xuegang Niu; Jiebo Li; Huimin Wang; Wen Huang; Chenyu Ding; Yuanxiang Lin; Yang Zhu; et al. (Chemical Engineering Journal, 2026)

Unveiling the superior Pb(II) affinity of sulfonic acid in functionalized UiO-66: A per-functional-group quantification strategy - Shuiping Yu; Yu Luo; Zhiwei Jin; Wenbao Li; Xianglin Zhong; Honggang Zhang; Xinggang Liu; Lin Ding; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2026)

Environmental stress drives microbial regime shifts and functional reorganization in a large deep reservoir - Xucong Lyu; Jing Dong; Xiaofei Gao; Jingxiao Zhang; Penghui Zhu; Haiyan Chen; Huatao Yuan; Yunni Gao; Xuejun Li; Senjie Lin (Environmental Research, 2026)

Construction of SnO2/Bi2O2CO3 Z-type heterojunction for photocatalytic degradation of humic acid under sunlight - Muxi Zhang; Chenchen Liao; Bin Dong; Wenjie Lin; Yu Chen; Penghui Yao; Xiaojie Sun; Hongxia Zhang (Environmental Research, 2026)

Online probabilistic forecast of landslide failure time via multi-information fusion - Mingxi Chen; Penghui Lin; Jie Jiang; Xiaoduo Ou; Qinghui Jiang; Xiaojie Tan (Engineering Geology, 2026)

A stable environmental niche for humans in the southern Levant 70–40 ka - Mahmoud Abbas; Zhongping Lai; Hua Tu; Xianjiao Ou; Paul A. Carling; Penghui Lin; Mohammad Alqudah; Bety S. Al-Saqarat; Ting Qiu; Michael D. Petraglia; Zeljko Rezek; John D. Jansen (Quaternary Science Reviews, 2026)

Biopolymer-based edible film incorporating Melaleuca Bracteata F. Muell. Essential oil with antimicrobial and antioxidant properties: A promising approach for strawberry fruit preservation - Jinjie Yang; Yaqian Niu; Penghui Hu; Yunqing Song; Ruihan Dang; Linke Li; Yuke Zhang; Yanshu Gong; Yixuan Lin; Ying Xin (Food Research International, 2026)

Effect of palladium loading on catalytic performance and product selectivity during diclofenac degradation by Pd0@anaerobic activated sludge - Xiaodi Li; Jingzhou Zhou; Lin Yang; Si Pang; Yi Yang; Defu Gan; Junxia He; Penghui Shi; Siqing Xia (Journal of Cleaner Production, 2026)

Alkali promotion in nonmetallic boron-based catalysts: Establishing structure–activity correlations for selective methane oxidation - Ran Yan; Penghui Li; Siyu Liu; Xindi Zhang; Leisu Li; Chenxin Zhang; Shaolong Wan; Jingdong Lin; Xiaodong Yi; Lingtao Liu; Shuai Wang (Chemical Engineering Journal, 2026)

Using statistical Change-Point Analysis to refine Holocene estuarine–deltaic transition - Penghui Lin; Guanjun Xu; Xianhe Zhang; Fang Li; Xiaolin Xu; Hongwei Li; Zhongping Lai (CATENA, 2026)

Robust deep reinforcement learning for improved energy-comfort performance in HVAC systems - Limao Zhang; Jing Guo; Chao Chen; Penghui Lin; Robert L.K. Tiong (Building and Environment, 2026)

The centennial legacy of disturbances on sedimentation and carbon burial in an estuarine mangrove ecosystem, South China - Juan Su; Yaobei Lin; Penghui Li; Zhangcai Qin; Luhua Xie; Fan Wang; Weiguang Li; Jinghong Zhang (Journal of Oceanology and Limnology, 2026)

Paleolakes in the lower Yellow River plain since the last deglaciation: age, distribution, and mechanism - Ruonan Tian; Bingpeng Yan; Chengguang He; Weitao Yuan; Penghui Lin; Yingjin Song; Bohui Liu; Yuexin Liu; Xiaodong Miao; Zhongping Lai (CATENA, 2025)

Study on soil improvement and microbial diversity restoration in metals-contaminated mining areas - Mingyu Xu; Yimei Zhang; Jiahui Zhao; Penghui Liu; Yi Pan; Wenting Lin; Acong Chen (Environmental Geochemistry and Health, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Luminescence dating of core DLC70-2 from the North Yellow Sea in China and its implication for late Quaternary transgressions - Nan Tang; Zhongbo Wang; Penghui Lin; Yuexin Liu; Zonghui Wu; Haozheng Tian; Xi Mei; Jun Sun; Jianghao Qi; Rihui Li; Shuyu Wu; Hongxian Chu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Natural borneol improves cellular uptake of curcumin to enhance its photodynamic bactericidal activity against Escherichia coli ATCC 8739 - Zhenlong Zhou; Ruoxin Chen; Pengzhen Li; Penghui Fan; Lin Ma; Xinyu Cai; Yuchao Hou; Binbin Li; Jianyu Su (Food Microbiology, 2025)

Structure optimization of a hydrocyclone for separation of recycled rubber particles with low-density difference - Long Li; Li Dai; Lin Zeng; Penghui Zhou; Jianping Li; Yulong Chang; Tong Zhang; Aosong Wei; Liang Ma; Hualin Wang (Process Safety and Environmental Protection, 2025)

Decade-long successive biochar amendment enhances wheat production and increases crop system resistance to unfavorable meteorological factors - Zhe Chen; Penghui Jin; Qi Liu; Yanhui Zhang; Tianlong Hu; Hui Wang; Rong Zhou; Jingru Zhang; Xingwu Lin; Zubin Xie (Field Crops Research, 2025)

Sustainable and selective upgrade of Cu(II) to High-Value HKUST-1 from acidic electroplating wastewater - Lin Ding; Qiang Wang; Yu Luo; Yunxia Luo; Wei Ren; Hui Shi; Penghui Shao; Xubiao Luo (Chemical Engineering Journal, 2025)

Efficient photocatalytic CO2 and Cr(VI) reduction on carbon quantum dots/carbon nitride heterojunctions - Zhengdong Xu; Xun Su; Penghui Yang; Junbo Zhong; Minjiao Li; Clemens Burda; Lin Dou (Fuel, 2025)

Selective anchoring of phosphate groups coupled with swift interlayer cation exchange for record-high capacity cobalt adsorption - Lingrong Zeng; Ziwei Yao; Dewei Li; Qingying Xiao; Ziwen Chang; Jingjing Fan; Shuigen Li; Mengling Li; Lin Ding; Penghui Shao; Xubiao Luo; Shenglian Luo (Resources, Conservation and Recycling, 2025)

Biological nitrogen fixation in paddy soils is driven by multiple edaphic factors and available phosphorus is the greatest contributor - Tianlong HU; Yanhui ZHANG; Hui WANG; Haiyang JIN; Benjuan LIU; Zhibin LIN; Jing MA; Xiaojie WANG; Qi LIU; Hongtao LIU; Zhe CHEN; Rong ZHOU; et al. (Pedosphere, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Composted maize straw under fungi inoculation reduces soil N2O emissions and mitigates the microbial N limitation in a wheat upland - Rong Zhou; Hui Wang; Jingru Zhang; Zhe Chen; Penghui Jin; Tianlong Hu; Qing Bian; Xingwu Lin; Xueqiang Zhao; Zubin Xie (Science of The Total Environment, 2024)

Direct recovery of high-purity lithium via nanofiltration membranes from leaching solution of spent lithium batteries - Shiweihua He; Qiuyang Zuo; Hui Shi; Zhiwei Geng; Congcong Liu; Lin Ding; Xin Li; Penghui Shao; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2024)

12-year continuous biochar application: Mitigating reactive nitrogen loss in paddy fields but without rice yield enhancement - Penghui Jin; Zhe Chen; Hui Wang; Runjin Lv; Tianlong Hu; Rong Zhou; Jingru Zhang; Xingwu Lin; Qi Liu; Zubin Xie (Agriculture, Ecosystems & Environment, 2024)

OSL and radiocarbon dating of core TBF-1 on the outer shelf of the East China Sea and implications for late Quaternary stratigraphic correlation - Zhongbo Wang; Nan Tang; Penghui Lin; Pengyu Qiao; Kai Lu; Xi Mei; Jun Sun; Jianghao Qi; Yang Wang; Hongxian Chu; Zhongping Lai (Quaternary Geochronology, 2024)

Neutrophil membrane-based biomimetic metal-polyphenol self-assembled nanozyme for the targeting treatment of early brain injury following subarachnoid hemorrhage - Wei Huang; Yu Tian; Jing Ma; Penghui Wei; Chengzhong Du; Xiaodan Zhang; Fuxiang Chen; Yuanxiang Lin; Yang Zhu; Dezhi Kang (Chemical Engineering Journal, 2024)

Sedimentation history linked to global change in the alpine Damqu Wetland of the Yangtze River headwater in interior Tibetan Plateau - Qinjing Shen; Xinqi Feng; Yinjun Zhou; Penghui Lin; Yuexin Liu; Yuansen Lai; Junfeng Han; YuJiao Liu; Yixuan Wang; Shuai Zhu; Zhijing Li; Zhongping Lai (Quaternary Geochronology, 2024)

Experimental study on direct shear properties and shear surface morphologies of hydrate-bearing sediments - Yajuan Zhang; Yanlong Li; Mingtao Chen; Lin Dong; Zhiyang Jiang; Kaixiang Shen; Penghui Zhang; Nengyou Wu (Gas Science and Engineering, 2024)

Orbital global change drove fluvial aggradation and incision in Tibetan upper Mekong river: Chronological perspectives - Yinjun Zhou; Junfeng Han; Qinjing Shen; Yantian Xu; Yaling Tao; Penghui Lin; Yuansen Lai; Yixuan Wang; Zhongping Lai (Quaternary Geochronology, 2024)

Chronology by luminescence and radiocarbon on core sediments from the northeastern pearl river plain and implications for delta process - Penghui Lin; Xian Hu; Weiqi Zhan; Yucong Chen; Ken Ling; Bingfa Zhi; Hongwei Li; Zhongping Lai (Quaternary Geochronology, 2024)

Determination of fatty acid uptake and desaturase activity in mammalian cells by NMR-based stable isotope tracing - Penghui Lin; James Sledziona; Kubra B. Akkaya-Colak; Maria M. Mihaylova; Andrew N. Lane (Analytica Chimica Acta, 2024)

Borneol serves as an adjuvant agent to promote the cellular uptake of curcumin for enhancing its photodynamic fungicidal efficacy against Candida albicans - Zhenlong Zhou; Shengli Wang; Penghui Fan; Xiaofeng Meng; Xinyu Cai; Wen Wang; Lin Ma; Hang Ma; Jianyu Su (Journal of Photochemistry and Photobiology B: Biology, 2024)

Predicting environmental risks of pharmaceutical residues by wastewater surveillance: An analysis based on pharmaceutical sales and their excretion data - Lihao Pang; Kai He; Yuxuan Zhang; Penghui Li; Yingchao Lin; Junjie Yue (Science of The Total Environment, 2024)

Association of residential greenness, air pollution with adverse birth outcomes: Results from 61,762 mother‑neonatal pairs in project ELEFANT (2011–2021) - Yuanyuan Yu; Huishu Lin; Qisijing Liu; Yuxuan Ma; Lei Zhao; Weixia Li; Yan Zhou; Hyang-Min Byun; Penghui Li; Chen Li; Congcong Sun; Xuemei Chen; et al. (Science of The Total Environment, 2024)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

Biochar application increases biological nitrogen fixation in soybean with improved soil properties in an Ultisol - Xingwu Lin; Zubin Xie; Tianlong Hu; Hui Wang; Zhe Chen; Rong Zhou; Penghui Jin (Journal of Soil Science and Plant Nutrition, 2023)

Highly effective recovery of palladium from a spent catalyst by an acid- and oxidation-resistant electrospun fibers as a sorbent - Nianshou Cheng; Lin Zhang; Mingyue Wang; Jiancheng Shu; Penghui Shao; Liming Yang; Xiaojing Meng; Yuzhu Fan; Min Li (Chemical Engineering Journal, 2023)

Late Pleistocene to Holocene sedimentary history in the Pearl River Delta revealed by OSL and radiocarbon dating - Penghui Lin; Yingjin Song; Weiqi Zhan; Ruonan Tian; Zhongbo Wang; Xiaolin Xu; Lan Luo; Mahmoud Abbas; Zhongping Lai (CATENA, 2023)

Exposure of ambient PM2.5 during gametogenesis period affects the birth outcome: Results from the project ELEFANT - Liqiong Guo; Huishu Lin; Hongyu Li; Xiaobin Jin; Lei Zhao; Penghui Li; Naiwei Xu; Song Xu; Junkai Fang; Shaowei Wu; Qisijing Liu (Environmental Research, 2023)

Integration of adsorption and simultaneous heterogeneous catalytic oxidation by defective CoFe2O4 activated peroxymonosulfate for efficient As(III) removal: Performance and new insight into the mechanism - Ziqun Lin; Fang Deng; Wei Ren; Zhongbing Wang; Xiao Xiao; Penghui Shao; Jianping Zou; Xubiao Luo (Chemical Engineering Journal, 2023)

Holocene sedimentary of the Pearl River Delta in South China: OSL and radiocarbon dating of cores from Zhuhai - Penghui Lin; Xiaolin Xu; Chaoyang Yan; Lan Luo; Mahmoud Abbas; Zhongping Lai (Frontiers in Marine Science, 2022)
Deltaic sediments provide a window for investigating delta development processes and the effects of human activities. Despite the fact that numerous studies have been conducted in the Pearl River Delta (PRD), the chronological data are still very limited, which hinder the detailed interpretation of the sedimentary records. The current study aims to establish high-resolution chronology on two cores from Zhuhai using quartz optically stimulated luminescence (OSL) and radiocarbon ( 14 C) dating and, further, to reconstruct the Holocene sedimentary history of the PRD. Core P1-1 has a depth of 79 m and core P3-2 a depth of 60 m. Thirteen quartz OSL samples from P1-1 produced ages between 10.4 and 0.16 ka. Eight OSL and eight 14 C ages from P3-2 span from 10.7 to 0.3 ka. The OSL and 14 C dates show a good agreement above the depth of 26 m (1.4–0.3 ka), but with discrepancies at depths of 26–54 m. 14 C ages (10.7–8.1 ka) are generally older (up to c. 2 ka) than quartz OSL ages, and the discrepancy decreases with depth. The age model shows three phases of the sedimentation process: (1) rapid accumulation rates of 7.48 (P1-1) and 7.52 (P3-2) m/ka between c. 10.7 and 7.5 ka in response to high sea level, (2) followed by a significantly reduced rate of 2.24 m/ka (P1-1) and a depositional hiatus (P3-2) from 7.5 to 2.5 ka as a result of reduced sediment supply and strong scouring by tidal processes, and (3) high sedimentation rates of 8.86 (P1-1) and 9.07 (P3-2) m/ka since 2.5 ka associated with intensive human activities and weakening tidal hydrodynamics. This sedimentary pattern is also evident in many other Asian deltas.

Analytical and experimental analysis of the shear strength of bolted saw-tooth joints - Hang Lin; Penghui Sun; Yifan Chen; Youyan Zhu; Xiang Fan; Yanlin Zhao (European Journal of Environmental and Civil Engineering, 2022)

High expression of NEK2 promotes lung cancer progression and drug resistance and is regulated by mutant EGFR - Chuanhui Chen; Shanshan Peng; Penghui Li; Lin Ma; Xin Gan (Molecular and Cellular Biochemistry, 2020)

Shear Behavior of Bolt-Reinforced Joint Rock Under Varying Stress Environment - Hang Lin; Penghui Sun; Yifan Chen; Yixian Wang; Yanlin Zhao (Geotechnical and Geological Engineering, 2020)

Ribosome profiling analysis identified a KRAS-interacting microprotein that represses oncogenic signaling in hepatocellular carcinoma cells - Wenli Xu; Bing Deng; Penghui Lin; Chang Liu; Bin Li; Qiaojuan Huang; Hui Zhou; Jianhua Yang; Lianghu Qu (Science China Life Sciences, 2020)

Catechins enhance skeletal muscle performance - Penghui Li; Ailing Liu; Wei Xiong; Haiyan Lin; Wenjun Xiao; Jianan Huang; Sheng Zhang; Zhonghua Liu (Critical Reviews in Food Science and Nutrition, 2020)

Bamboo shoot skin: turning waste to a valuable adsorbent for the removal of cationic dye from aqueous solution - Lin Zhu; Penghui Zhu; Liangjun You; Songjun Li (Clean Technologies and Environmental Policy, 2019)